Dichloroacetate prevents TGFβ-induced epithelial-mesenchymal transition of retinal pigment epithelial cells. (August 2020) - Shukal, Dhaval; Bhadresha, Kinjal; Shastri, Bhoomi; Mehta, Deval; Vasavada, Abhay; Johar SR, Kaid
Abstract: Proliferative retinopathies are associated with formation of fibrous epiretinal membranes. At present, there is no pharmacological intervention for the treatment of retinopathies. Cytokines such as TGFβ are elevated in the vitreous humor of the patients with proliferative vitro-retinopathy, diabetic retinopathy and age-related macular degeneration. TGFβ isoforms lead to epithelial-mesenchymal transition (EMT) or trans-differentiation of the retinal pigment epithelial (RPE) cells. PI3K/Akt and MAPK/Erk pathways play important roles in the EMT of RPE cells. Therefore, inhibition of EMT by pharmacological agents is an important therapeutic strategy in retinopathy. Dichloroacetate (DCA) is shown to prevent proliferation and EMT of cancer cell lines but its effects are not explored on the prevention of EMT of RPE cells. In the present study, we have investigated the role of DCA in preventing TGFβ2 induced EMT of RPE cell line, ARPE-19. A wound-healing assay was utilized to detect the anti-EMT effect of DCA. The expressions of EMT and cell adhesion markers were carried out by immunofluorescence, western blotting, and quantitative real-time PCR. The expression of MAPK/Erk and PI3K/Akt pathway members was carried out using western blotting. We found that TGFβ2 exposure leads to an increase in the wound healing response, expression of EMT markers (Fibronectin, Collagen I, N-cadherin, MMP9, S100A4, α-SMA, Snai1, Slug) and a decrease in the expression of cell adhesion/epithelial markers (ZO-1, Connexin 43, E-cadherin). These changes were accompanied by the activation of PI3K/Akt and MAPK/Erk pathways. Simultaneous exposure of DCA along with TGFβ2 significantly inhibited wound healing response, expression of EMT markers and cell adhesion/epithelial markers. Furthermore, DCA and TGFβ2 effectively attenuated the activation of MAPK/Erk/JNK and PI3K/Akt/GSK3β pathways. Our results demonstrate that DCA has a strong anti-EMT effect on the ARPE-19 cells and hence can be utilized as a therapeutic agent in the prevention of proliferative retinopathies. Highlights: Epithelial-mesenchymal transition (EMT) of retina pigment epithelial (RPE) cells is important in the development of proliferative retinopathies. DCA inhibits TGFβ–induced EMT in ARPE-19 cells as evident by reduced wound healing and expression of EMT markers. Anti-EMT effect of DCA on ARPE-19 cells is also associated with the modulation of MAPK/Erk and PI3K/Akt pathways.